Otoritarianisme Lokal sebagai Ancaman terhadap Demokrasi Desa: Manipulasi Elektoral, Patronase, dan Identitas Lokal dalam Pemilihan Kepala Desa di Pucangrejo, Kendal - Mukhammad Akhmad Najich Alfayn; Solkhah Mufrikhah (Nakhoda: Jurnal Ilmu Pemerintahan, 2026)
This study examines the dynamics of local authoritarianism in the 2022 village head election in Pucangrejo, Kendal regency, Central Java, where formally democratic procedures were implemented while substantive democratic practice was distorted. Over 4 months of fieldwork, data were collected through in-depth interviews, participant observation, and document analysis within a qualitative case-study design. Informants included candidates, election committee members, and residents. The results indicate that elite actors exploited electoral rules—particularly the Computer Assisted Test, which produced two conflicting declarations of results—to sideline the leading rival candidate. These practices extended to institutional co-optation, as the election committee cooperated with informal elites, and to patronage networks and development narratives deployed to secure loyal voters. Organized opposition to outsider candidates, reinforced by local identity resistance to incorporation, further entrenched exclusionary political norms. The findings suggest that village-level elections risk subordination to elite control, and they point to the need for third-party monitoring and more robust institutional safeguards to protect grassroots democratic autonomy.